Efek Misoprostol Sublingual pada Kasus Blighted Ovum dan Missed Abortion - Agoes Oerip Poerwoko; Anantyo Binarso Mochtar; Hary Tjahjanto (MEDIA MEDIKA INDONESIANA, 2008)
Sublingual misoprostol effect in blighted ovum and missed abortion casesBackground: Misoprostol, a prostaglandin E1 analog is widely used especially during first and second trimester as a cervical ripening before curretage as well as medical abortion without curretage. Misoprostol dosage and mode of administration are still an interesting study. Sublingual administration of misoprostol needs further study.Objective: To evaluate the effect and side effect of repeated dosage of 400 g misoprostol administered sublingually at four-hourly interval up to a maximum of two doses in total for the treatment of blighted ovum and missed abortion.Methods: A pseudo clinical trial was done to all patients diagnosed to have blighted ovum and missed abortion coming to Dr. Kariadi Hospital between March and July 2005. Patients were given sublingual 400 g misoprostol. Evaluation were done every 4 hours toward blood pressure, heart rate and body temperature and other major complaints. Descriptive analysis was carried to the available data.Results: Mean time interval between drug administration and uterine contraction achieved for 187.5 (115.4) minutes. Mean time interval of drug administration and the expulsion of product of conception achieved for 300.6 (118.5) minutes. Cervical dilatation in patient with no product of conception expulsion were 9.1 (1.3) mm and median 9.0 (range: 7-12) mm. Sublingual misoprostol found to dilate a cervix without expulsion of product of conception in 51.4% of subject and expulsion of product of conception in 48.6%with side effect of shivering in 11.4%, headache 8.6%, nausea 5.7% and vomiting 2.9%.Conclusion: Sublingual misoprostol dilates cervix with and without product of conception expulsion and gives mild side effect.Keywords: Sublingual misoprostol, blighted ovum, missed abortion.ABSTRAKLatar belakang: Misoprostol, suatu analog prostaglandin E1 telah dipakai secara luas di bidang obstetri ginekologi pada kehamilan trimester I dan II untuk pematangan serviks sebelum tindakan kuretase sampai tindakan aborsi medis tanpa kuretase. Jalur atau cara pemberian misoprostol serta dosis misoprostol sampai saat ini masih menarik untuk menjadi bahan penelitian. Salah satu diantaranya adalah pemberian misoprostol secara sublingual.Tujuan: Meneliti efek dan efek samping misoprostol sublingual 400 g dosis ulangan dengan interval 4 jam maksimal dua kali pemberian pada kasus blighted ovum dan missed abortion.Metode: Studi bersifat eksperimen klinik tanpa pembanding dengan subyek penelitian semua pasien dengan blighted ovum dan missed abortion pada bulan Maret sampai dengan Juli 2005 di RS Dr. Kariadi Semarang. Diberikan 400 g sublingual dengan evaluasi tiap 4 jam terhadap tekanan darah, frekuensi nadi, suhu tubuh dan keluhan lainnya. Uji statistik deskriptif dilakukan terhadap semua data yang ada.Hasil: Didapatkan rerata interval waktu antara saat pemberian obat sampai timbulnya kontraksi uterus 187,3 (115,4) menit, rerata interval waktu antara saat pemberian obat sampai timbulnya pengeluaran jaringan 300,6 (118,5) menit. Dilakukan pengukuran dilatasi serviks pada subyek yang tidak terjadi pengeluaran jaringan didapatkan rerata dilatasi serviks sebesar 9,1 (1,3) mm dan median 9,0 (range: 7–12 mm). Secara keseluruhan misoprostol sublingual menimbulkan dilatasi serviks tanpa pengeluaran jaringanhasil konsepsi pada 51,4% subyek dan terjadinya pengeluaran jaringan hasil konsepsi pada 48,6% subyek. Efek samping yang timbul adalah menggigil (11,4%), pusing (8,6%), mual (5,7%) dan muntah (2,9%).Simpulan: Misoprostol sublingual menimbulkan dilatasi serviks tanpa dan dengan pengeluaran jaringan hasil konsepsi serta menimbulkan efek samping ringan.